Public Art and Space Environment Design Using Genetic Algorithm-Guided 3D Virtual Reconstruction. - Luo, Man (Journal of Environmental & Public Health, 2022)
Public art plays a crucial role in influencing the development of the urban space environment by embodying the spiritual outlook and cultural heritage of a city. The research status and development trend of contemporary public art and space environment design are introduced in this article. In this essay, the relationship between public art and the environment of public spaces is examined in terms of type, status quo, and impact. The requirements of the virtual process are then thoroughly examined through the practical application of various collaborative software based on the actual needs of 3D virtual reconstruction. In parallel, a genetic algorithm-based optimization design scheme for the space environment is proposed. Numerous experiments are conducted to confirm the viability of this method. The efficiency of this algorithm, according to experiments, is very high, reaching 94.87 percent. The scores of the residents are also good as a result of this article's design. This demonstrates the validity of this approach. The study of public art and urban space environment design is expected to contribute positively to the growth of the city.